Therapeutic Embolization - Varghese, Kiron; Adhyapak, Srilakshmi (Springer International Publishing : Imprint: Springer, 2017)
This book is a concise guide to vascular embolization and provides a perspective to the operator regarding embolization procedures in various clinical settings. This procedure has gained acceptance in terms of safety and efficacy with the advent of more advanced hardware like microcatheters, embolization materials and high resolution digital imaging. It is especially useful in patients with several critical co-morbid medical conditions which preclude radical surgeries as it is organ preserving, with limited complications. Therapeutic Embolization discusses indications for the procedure, materials used, established techniques, complications and outcomes of embolization in a detailed but practical manner. While it does not claim to be a comprehensive textbook, it concentrates on providing clinically relevant information on the technique suitable for cardiologists and radiologists training to use the techniques.